IMPLEMENTASI PERPAJAKAN DALAM USAHA JASA KONSTRUKSI PERENCANAAN, PELAKSANAAN DAN PENGAWASAN - Atika Ira Mahera (Politeknik Keuangan Negara STAN, 2022)
A construction services business is a consulting service for planning,implementing, and supervising construction work. Construction serviceentrepreneurs have different tax rates by looking at the work done.Construction service business actors and tax researchers often feelconfused in calculating the construction service business tax. This studyaims to straighten out the differences in articles that are oftenconsidered confusing. The method in writing is a quantitative method byconducting a literature study and using secondary data. The reason forusing secondary data is that data is easier to obtain and written datausually goes through a lot of selection research. In writing, it is definitelytrustworthy and minimal fraud. The study results show that differencesin the planning, implementation and supervision systems in theconstruction service business involve the condition of companies thathave SIUJK and SBU or those that do not have SIUJK and SBU that thetax on each activity gets different tariff treatment. The writing isexpected to be a reference for students who want to know aboutconstruction services and taxes. The writing is also expected to be areference for prospective construction service entrepreneurs who arejust starting to find out the problems and the imposition of taxes thatwill be faced in their efforts to comply with applicable tax regulations.